Kejenuhan Belajar dan Prokrastinasi Akademik terhadap Kemampuan Pemecahan Masalah Matematika: Learning Burnout and Academic Procrastination on Mathematical Problem Solving Ability - Friantini, Rizki Nurhana; Sugiharto, Sugiharto; Pinardi, Janu; Winata, Rahmat; Yupito, Yupito; Suparman, Suparman (​Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
This study used multiple linear regression data analysis techniques to determine the effect of learning burnout and academic procrastination of students, both individually and together, on mathematical problem-solving abilities. The study was conducted on 88 students of class X of SMA Muhammadiyah 1 Palangka Raya, who were selected by simple random sampling. Data collection used a test for problem-solving abilities and a questionnaire for each learning burnout and academic procrastination. Before conducting multiple linear regression, prerequisite tests were carried out, namely: normality test, heteroscedasticity test, linearity test, autocorrelation test, and multicollinearity test. After meeting the prerequisite tests, the analysis was carried out and the results obtained were that there was an effect of learning burnout on students' mathematical problem-solving abilities, there was an effect of academic procrastination on students' mathematical problem-solving abilities, and there was an effect of learning burnout and academic procrastination together on the mathematical problem-solving abilities of class X students of SMA Muhammadiyah 1 Palangka Raya.